TRANSITIVITY ANALYSIS OF NARRATIVE TEXT “ISSUMBOSHI” IN ENGLISH TEXTBOOK - Dedeh Hayati; Rama Dwika Herdiawan; Raynesa Noor Emiliasari (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2022)
Abstract This study aims to identify and describe the type of transitivity that appeared in the Narrative text titled